Fast algebraic decoding of the (17, 9, 5) quadratic residue code - Hung-Peng Lee (2012 2nd International Conference on Consumer Electronics, Communications and Networks, 2012)
A fast algebraic decoding algorithm is proposed to correct all patterns of two or fewer errors in the binary (17, 9, 5) quadratic residue (QR) code. Computer simulations show that the average decoding time of the proposed decoding algorithm is about 2.88 times less execution time than the D3 algebraic decoding algorithm of Chang et al.